Serum Aminoacyl-tRNA Synthetase-Interacting Multifunctional Protein-1 Can Predict Severe Antineutrophil Cytoplasmic Antibody-Associated Vasculitis: A Pilot Monocentric Study. (20th May 2019) - Ahn, Sung Soo; Kim, Jin-Ock; Yoon, Taejun; Song, Jason Jungsik; Park, Yong-Beom; Lee, Sang-Won; Park, Sang Gyu
Abstract : We investigated whether serum aminoacyl-tRNA synthetase-interacting multifunctional protein-1 (AIMP1) could predict severe cases of antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) based on the Birmingham vasculitis activity score (BVAS). Sixty-one patients with AAV were selected for inclusion from our prospective AAV cohort. AAV-specific indices and clinical manifestations were assessed, and laboratory tests were performed on the day of blood sampling. Patients with severe AAV were defined as those with a BVAS higher than the lower limit of the highest tertile of BVAS (BVAS ≥ 12). We measured serum AIMP1 levels of the stored serum samples. A total of 20 (32.8%) and 41 (67.2%) patients were classified as having severe and nonsevere AAV according to the cut-off of BVAS ≥ 12. Patients with severe AAV showed higher frequencies of general and renal manifestations, along with ANCA positivity, and exhibited a higher mean neutrophil count, erythrocyte sedimentation rate, and C-reactive protein levels, but lower mean haemoglobin and serum albumin levels than those with nonsevere AAV. The mean serum AIMP1 level in patients with severe AAV was significantly higher than that of patients with nonsevere AIMP1 (351.1 vs. 98.4 pg/mL, p = 0.006). Multivariate logistic regression analysis including variables showing significance in univariate analyses revealed that only serum AIMP1 exhibited a significant association with severe AAV (odds ratio 1.004, p = 0.031). When we set the optimal cut-off of serum AIMP1 for severe AAV to 50.28 pg/mL, patients with severe AAV more frequently had AIMP1 levels above the cut-off than those with nonsevere AAV (80.0% vs. 31.7%, relative risk 8.615, p < 0.001). The results from our study suggest that serum AIMP1 can be used to estimate the cross-sectional severe AAV population based on the BVAS.